The Stone that the Builders Rejected: Work, Empire, and the Two Faces of the Bible. Issue 3 (3rd September 2015) - Rose, Marika
Abstract : This paper interrogates the liberationist vision of Sandford's 'Luxury Communist Jesus', the reactionary Jesus of Myles' 'Opiate of Christ' and the imperialist chronologies of Wan's 'Reflections on Empire' in relation to broader questions concerning the ambiguities of scriptural hermeneutics and the complex relationship of Christianity to capitalism.